2020
DOI: 10.3390/antibiotics9050229
|View full text |Cite
|
Sign up to set email alerts
|

Omics for Bioprospecting and Drug Discovery from Bacteria and Microalgae

Abstract: “Omics” represent a combinatorial approach to high-throughput analysis of biological entities for various purposes. It broadly encompasses genomics, transcriptomics, proteomics, lipidomics, and metabolomics. Bacteria and microalgae exhibit a wide range of genetic, biochemical and concomitantly, physiological variations owing to their exposure to biotic and abiotic dynamics in their ecosystem conditions. Consequently, optimal conditions for adequate growth and production of useful bacterial or microalgal metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 162 publications
0
28
0
Order By: Relevance
“…Several studies have performed an integrated metabolomics-proteomics, which could show a better landscape of the marine plankton [81,82]. Integrating "-omics" studies (e.g., genomics, proteomics, transcriptomics, metabolomics, lipidomics, and glycomics) will enable the investigation of the impacts of ecological interactions on organism physiology as well as evaluation of physiological and biochemical properties relating to human health for future applications [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have performed an integrated metabolomics-proteomics, which could show a better landscape of the marine plankton [81,82]. Integrating "-omics" studies (e.g., genomics, proteomics, transcriptomics, metabolomics, lipidomics, and glycomics) will enable the investigation of the impacts of ecological interactions on organism physiology as well as evaluation of physiological and biochemical properties relating to human health for future applications [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an increased abundance of environmental stress sensing genes, particularly in the rhizosphere microbiome of ARD soils compared to ARDunaffected soils, was recently unraveled by a metagenomics approach (Radl et al, 2019). Against this background, in the present study, we aimed to study apple root-associated endophytic S. pulveraceus ES16 by employing a chemical OSMAC approach (Romano et al, 2018;Pan et al, 2019;Maghembe et al, 2020) to induce high stress and sporulation in the organism. Earlier studies have substantiated that Streptomyces species are stressed and forced to sporulate by regulation of the pleiotropic transcriptional factors such as GlnR, MtrA, and PhoP, which can be achieved by manipulating the nature of carbon and nitrogen sources, their quantity (specifically the carbon/nitrogen ratio as well as their depletion), and phosphate availability in the medium (Karandikar et al, 1996;Martín and Liras, 2020).…”
Section: Phenotypic Differentiation Of Endophytic S Pulveraceus Es16mentioning
confidence: 99%
“…In the present study, the phenotypic observations of endophytic S. pulveraceus ES16 under specific OSMAC parameters revealed an earthy soil odor release during this bacterium's prolific sporulation on PDA plates that induced stress to the organism. One important reason why we employed the six different defined media conditions to cultivate the organism was to study its secreted volatilome and metabolome expressed under the influence of stressful media conditions compared to nutrient-rich and optimum conditions (Romano et al, 2018;Pan et al, 2019;Maghembe et al, 2020). OSMAC-guided SPME-GC-MS analyses further revealed that the organism produces the volatile signal compound geosmin (compound 1, Figure 3; γ εω-"geo": earth, oσ µη-"osmi": smell) only under stressful conditions and during sporulation, and it is responsible for this scent.…”
Section: Endophytic S Pulveraceus Es16 Produces the Volatile Semiochmentioning
confidence: 99%
See 2 more Smart Citations